Dorsal Augmentation with Homologous Rib - Kridel, Russell W. H.; Sturm, Angela K. (Facial Plastic Surgery, 2017)
Dorsal augmentation grafts are used to reconstruct and raise the nasal dorsum in patients with dorsal saddling due to trauma, infection, or previous nasal surgery, as well as in patients with a narrow, congenitally low, and/or wide dorsum. Alloplastic implants and various biomaterials are available for grafting, each with advantages and disadvantages. Although autologous septal cartilage is a preferable and often convenient source of cartilage, it is frequently not sufficient for large volume dorsal augmentation, nor is it available in patients who have had septoplasty, infection, previous rhinoplasty with grafting, or significant trauma. Ear cartilage may be used but it is difficult to make homogenous and smooth, and dorsal irregularities can be seen in the long term especially in thin-skinned patients. For these reasons, we frequently use irradiated costal cartilage from tissue banks as our grafting source, thereby eliminating the morbidity of harvesting the patient's own rib. Proper surgical techniques, the use of antibiotics, and proper sculpting and placement of the cartilage limits complications such as warping, resorption, infection, and extrusion. Irradiated homograft costal cartilage grafts have been used successfully in large numbers of patients with long-term follow-up with low complication rates and serve as a welcome alternative to harvesting a patient's rib cartilage.
Keywords: dorsal augmentation graft; irradiated homograft costal cartilage; dorsal saddling; revision rhinoplasty; homologous rib graft